Learning Independence and Family Support as Predictors of Student Academic Success in the Digital Independent Learning Era - Masfufah Masfufah; Didit Darmawan (Molang: Journal Islamic Education, 2024)
The phenomenon of declining learning discipline, the tendency to depend on instant learning resources, and the gap in students' ability to manage independent learning strategies are important concerns in the university environment. These challenges are increasingly complex in the era of digital independent learning, where students are required to be able to manage time, filter digital information, and maintain motivation to learn in the midst of various technological distractions. This condition is strengthened by the fact that there is still a variety of family support that affects students' mental and academic readiness, including the support of technology facilities and the strengthening of emotional factors. This situation shows the urgency of research on internal and external factors that affect learning outcomes. This study aims to analyze the influence of learning independence and family support on student learning outcomes. The research approach used was quantitative with an explanatory design, involving 100 students through convenience sampling. The analysis includes descriptive statistics, validity tests, reliability tests, and multiple linear regressions. The results showed that learning independence and family support had a significant positive effect on learning outcomes, with learning independence as the most dominant variable. These findings emphasize the need to strengthen learning programs that encourage academic independence, digital literacy, and family collaboration to support student development in a technology-based learning environment.